Risk management: advancing strategic risk management research tool / Aloysius Harry Mukti and Oswald Timothy Edward - Edward, Oswald Timothy; Mukti, Aloysius Harry (Universiti Teknologi MARA Cawangan Johor, 2024)
Risk management is the practice of identifying, analyzing, and responding to risk factors throughout the life of a project and in the best interests of its objectives. Proper risk management implies control of possible future events and is proactive rather than reactive. By managing risks effectively, organizations can reduce the likelihood and impact of negative outcomes, as well as capitalize on opportunities that may arise. This involves processes such as risk identification, assessment, prioritization, and the implementation of strategies to mitigate or manage these risks using resources efficiently and cost-effectively. Strategic risk management, a specific area of risk management, focuses on risks that affect the high-level goals and objectives of an organization. This approach integrates risk management with strategic planning and decision making, ensuring that risks are considered in the context of an organization’s overarching strategies and its external environment. Research in strategic risk management typically explores how organizations can align their risk appetite with their strategic goals, assess potential impacts on their strategic objectives, and create flexible strategies to adapt to changing conditions. This research is crucial for organizations aiming to achieve a sustainable competitive advantage and resilience against unforeseen challenges.